Origin and Recharge Area Determination of Springs Around a Lake for Sustainability of the Lake - Paston Sidauruk; Rasi Prasetio; . Satrio; Evarista R. Pujiindiyati (Journal of Human, Earth, and Future)
The springs surrounding the lake may be the lake's leakage or groundwater outlets that were replenished by precipitation in the mountain. The springs’ source is crucial to the lake’s water balance and, thus, to its sustainability. The water level in Lake Toba has fluctuated. The water level differential between the lowest and maximum can be as much as three meters. Springs with flow rates ranging from 2 to 5 m3/s were discovered downstream of the lake. The origin of these springs is not known yet. At one point, the locals blamed these springs for the lake's unstable water level. This study's goal is to determine if the springs came from a lake leak or from other sources, such as local groundwater. Water samples from lakes, springs, surface waters, and precipitations were taken on a regular basis. Using hydrochemical and stable isotope variations of all samples, the relationships between the springs and lake are examined. The assessment of the data showed that the lake was not the source of springs. The springs were groundwater's outlets that recharged by precipitation on Mount Simarjarungjung, which is located between 1700 and 1900 meters above sea level. These results suggest that the primary causes of lake water level fluctuation may be the reduction in groundwater flow in the lake's catchment area brought on by deforestation and changes in land use. The water flowing down the Asahan River to fuel the INALUM aluminum smelting business in the region could be the other issue.